Exploring Female Sexual Offending with The Concepts of Hypersexuality and Atypical Psychotic Disorder - Doğan, Mehmet; Boylu, Muhammed Emin; Taşdemir, İlker; Saygılı, Sefa (Wiley, 2025)
Sexual offending is often perceived as predominantly a male behavior. However, due to growing public interest in female criminality, research on female offenders is increasing. Sexual offending can be influenced by various factors, such as hypersexual disorder (HSD), or may be associated with psychiatric conditions like borderline personality disorder (BPD). In this case, a 46-year- old woman was charged with a sexual offense for engaging in sexual intercourse with four underage male adolescents. She had a medical history of mood disorder and alcohol abuse. During her psychiatric evaluation in our unit, it was observed that she exhibited poor self-care, appeared older than her age, had an inappropriate affect, and impoverished thought content. She was subsequently diagnosed with “atypical psychosis” and deemed not criminally responsible by the decision of the committee by majority vote. This case highlights that sexual abuse against children is much rarer among women compared to men. As the number of studies on this topic increases, our understanding will improve, providing guidance for preventing recidivism, and aiding in the treatment and appropriate reintegration of women who perpetrate sexual offenses into society.
Keywords: Borderline Personality Disorder; Child Abuse; Criminal Responsibility; Female Sexual Offender; Forensic Psychiatry; Sexual Offense